Exploring the intersectional psychosocial impact of epilepsy in Nepal: a gender lens approach - Swastika Shrestha; Safal Kunwar; Reshu Parajuli; Hemav Rajbhandari; Raghu Dhital; Poonam Rishal; Maxine Caws (Social Sciences and Humanities Open)
Introduction: Epilepsy impacts multiple aspects of the lives of people living with epilepsy (PLWE). We explored the psychosocial impact of the disease on the lives of PLWE in Nepal and the intersectionality of impacts with gender. Methods: In-depth interviews were conducted between March 2023 and June 2023 with twenty participants (10 male and 10 female) receiving treatment for epilepsy at Kathmandu Medical College (KMC) and Nepal Epilepsy Association (NEA). A rich account of the participants’ lived experiences was explored through probing and intuition. Data were explored using thematic analysis. Results: Stigma associated with epilepsy was the most common factor affecting the quality of life (QoL) of PLWE. The psychosocial impacts of epilepsy included limited employment and educational opportunities, limited socializing, inability to drive vehicles, inability to engage in sports and activities such as swimming. Epilepsy and anti-seizure medication (ASM) had marked effects on the sexual and reproductive health (SRH) of the participants. Women living with epilepsy (WLWE) reported more SRH problems than men. Participants adopted various coping mechanisms to deal with the disease. A greater proportion of male participants mentioned actively adopting coping mechanisms to improve their QoL with epilepsy. Epilepsy affected the interpersonal relationships of PLWE, especially spousal relationships and friendships. The negative impact on spousal relationships was more severe for women than for men living with epilepsy. Access to effective ASM mitigated many of the most severe impacts for PLWE. Conclusion: Social factors, specifically stigma associated with epilepsy, have important multidimensional effects on the QoL of PLWE. Seizure control through appropriate ASM is a critical factor in obtaining high QoL. Experiences of PLWE are strongly gendered. Women report more psychosocial and biological (reproductive) impact of the disease, while men are more proactive in adopting active coping mechanisms to deal with the disease. Establishing strong psychosocial support systems is critical to improving QoL of all PLWE.